Sovereign Power and Nuda Vita in Ruta Sepetys’s I Must Betray You: Unveiling the Struggles of Romanian Civilians In 1989 - Rizki, Geubrina; Huda, Miftahul; Aziz, Abdul (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
I Must Betray You (2022), a literary work by Ruta Sepetys, is a touching drawing of the painful experience suffered by Romanian civilians under Nicolae Ceauşescu’s regime in 1989. Through a rich tapestry of policies, regulations, and prohibitions, Ceauşescu bound Romanian life to nuda vita. This study aims to analyzes how Ruta Sepetys’ I Must Betray You illustrated the sovereign power that restrains Romanian civilians’ lives and how the civilians detached from nuda vita and the sovereign power. It employs a qualitative descriptive approach by drawing on the theoretical framework put forth by Giorgio Agamben. The framework encompasses crucial concepts such as sovereign power, the state of exception, and nuda vita. Notably, the sovereign power represents an authority to create laws but remains unbound. The state of exception refers to a blurred zone of “law and life”. Besides, nuda vita embodies the condition in which an individual’s life is vulnerable to death without being considered a sacrifice. The study reveals two primary findings. First, restrict any criticism directed at Ceauşescu, exiting Romania, gathering in groups of more than three individuals, engaging in conversations with foreigners, possessing typewriters, and many other prohibitions. The authorities also exercised rigid control over civilians’ basic needs, from access to electricity to food, and imposed strict laws. The sovereign power restrained Romanian civilians’ lives through various methods to instill fear, such as utilizing Phillips, i.e., tapping devices, widely spread within households. Second, the civilians’ revolts against the sovereign power and nuda vita were manifested through strategies like adopting a double-agent role, utilizing knowledge as propaganda, and building allies with soldiers. The novelty of this study proposes a path towards detachment from the sovereign power and nuda vita, particularly relevant to contemporary debates.